The Effect of Spiritual Group Therapy on Reducing Death Anxiety in Patients with Chronic Kidney Failure - Zuliya Indah Fatmawati; Wahyudi Qorahman MM (Indonesian Journal of Global Health Research, 2024)
Chronic kidney failure can cause various complications, including complications in physiological disorders and psychological disorders. Complications in terms of psychology can be influenced by predisposing factors, including feelings of uncertainty about health conditions, choices and treatment results. Every one patients with chronic kidney failure undergoing hemodialysis usually has a different response to the disease process being experienced, especially from a psychological perspective. The patient's understanding of the limited time they have makes the patient death anxiety experience. Objective: The aim of this study was to reduce death anxiety in patients with chronic kidney failure undergoing hemodialysis Results: There is a difference in DAS (death anxiety scale) before and after the intervention. The results of the study using the Mann-Whitney statistical analysis test showed a difference in the Death Anxiety Scale (DAS) with a P value of 0.000 between the intervention group and the control group after treatment.. Conclusions : Spiritual group therapy is effective in reducing DAS levels in patients with chronicrenal failure undergoing hemodialysis. In accordance with the purpose of providing group spiritual therapy, the mechanism for reducing anxiety by involving patients with chronic kidney disease includes discussion sessions where patients can encourage each other, exchange information, and pray together, thereby helping to alleviate the mental burden that causes anxiety.